Application of IMB model in preventing venous thromboembolism in elderly lung cancer patients - Liu, Mengdan; Chen, Xushu; Ma, Peng; Yang, Zhuoxin; Jiang, Min; Deng, Min (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aims to explore the effects of the Information-Motivation-Behavioral (IMB) Skills Model on the prevention of Venous Thromboembolism (VTE) in elderly lung cancer patients. Methods A convenience sampling method was used to select study participants who were hospitalized for treatment between November 2022 and August 2023 at a tertiary hospital in Neijiang and met the inclusion and exclusion criteria. The control group (n = 41) received conventional health education, while the intervention group (n = 40) received health education based on the IMB Skills Model over three months. The scores of the Venous Thrombosis Knowledge, Participation in Thrombosis Prevention Willingness and Behavior Questionnaire, and Quality of Life Measurement Scale (QLQ-C30) were compared before the intervention and after three months. After three months of intervention, the hospital satisfaction and VTE incidence rates in both groups were investigated and compared. Results After three months of intervention, the scores for the Venous Thrombosis Knowledge, (Participation in Thrombosis Prevention Willingness and Behavior Questionnaire in the intervention group were higher than those in the control group (P < 0.05). The QLQ-C30 scores in the intervention group for physical function, role function, emotional function, insomnia, appetite loss, and overall health status were higher than those in the control group (P < 0.05). The intervention group rated higher in doctor's professional skills, information provision, accessibility; nurse's professional skills, humanistic care, information provision, accessibility; team communication, services of other personnel, overall satisfaction compared to the control group (P < 0.05). The rate of VTE in the intervention group was 2.5%(1/40), and that in the control group was 19.5%(8/41). There was a significant difference (χ2 = 4.336, P = 0.037). Conclusion Nursing interventions based on the IMB Skills Model for elderly lung cancer patients can enhance patients’ understanding of venous thrombosis, increase willingness and active participation in thrombosis prevention, improve quality of life, increase hospital satisfaction, and reduce the incidence of VTE.